UPAYA PEMERINTAH DALAM MENANGGULANGI KEMISKINAN - Nur masyitah (Universitas Syiah Kuala, 2022)
The state of poverty is generally measured by income levels. The income of a household can be derived from three sources: the effort, the work, and the acquisition of the asset portion. Very few poor households have income-generating assets. The first source of income, which is to try with a very small scale and/or work as a laborer, these two things are most likely to be improved, especially for those who really want to work and try. As the organizer of the government is obliged to carry out the mandate of the Act to alleviate poverty. Efforts made especially by local governments are set out in strategic programs to tackle poverty. Plans to tackle poverty and create employment opportunities have been undertaken by governments together with communities through the development and implementation of various poverty reduction programs. The program includes good efforts through the provision of food, health and education services, expansion of employment opportunities, agricultural development, provision of revolving funds as venture capital, construction of basic facilities and basic facilities and business assistance. The government has been working hard to tackle poverty and reduce unemployment. This is realized through the implementation of poverty alleviation programs, especially community empowerment programs and community self-reliance programs through business assistance and credit/working capital assistance.